Dialectal intelligibility of Assamese tested functionally - Qamri, Sabbah (Indian Journal of Language and Linguistics, 2021)
This paper includes a detailed discussion on the intelligibility of the speakers of four regional dialects of the Indo-Aryan language of Assamese. Prior research on Assamese dialects mostly being confined to examining structural variation lends this study relevance and urgency. The dialects of Standard Assamese, Central Assamese, Kamrupi, and Goalparia, covering three varieties each, were considered for the study. Using a functional intelligibility testing approach, the rate of overall intelligibility as well as of inter- and intra-dialectal mutual intelligibility of the dialects were determined. 24 speakers (1 male and 1 female from each variety) were asked to record ‘texts’— words, sentences, and connected speech in their native varieties of Assamese. 11 listeners from each variety (132 in total) were then tested on their comprehension of texts from non-native varieties. Thereafter, their rates of comprehension were used to determine the rates of mutual intelligibility between speakers of the different dialects and varieties of Assamese. This paper establishes that the rates of mutual intelligibility are unequal and asymmetric among the dialects— the native speakers of the Standard and Central Assamese dialects were more intelligible to the speakers of Kamrupi and Goalparia than vice-versa. Finally, the paper finds that the rate of intelligibility is the lowest for words in isolation and reinforces the important role of context in intelligibility.